Potential of Meniran (Phyllanthus niruri L.) and Sambiloto (Andrographis paniculata) as a Supplement to the Management of Coronavirus Disease 2019 (COVID-19) - Rachmat Hidayat; Patricia Wulandari (Eureka Herba Indonesia, 2022)
COVID-19 infection with moderate or severe symptoms can cause pneumonia with an opaque appearance that can be detected on a chest CT scan, pulmonary edema, and accumulation of pleural fluid in the lungs. The use of herbs as health drinks is thought to play a role in increasing the body's immunity. Meniran plant (Phyllantus niruri) contains tannins and flavonoids, which are efficacious as immunomodulators. Meanwhile, sambiloto also contains chemical compounds of alkaloids, carbohydrates, resins, saponins, flavonoids, steroids, glycosides, and tannins. Meniran and sambiloto herbs have the potential to increase the system potential to be developed as a supplement to treat COVID-19.